PENGARUH PERPUTARAN KAS DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN PLASTIK DAN KEMASAN YANG TERDAFTAR DI BEI - Jufrizen . (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
This study aims to determine the effect of cash turnover and inventory turnover either partially or simultaneously tehadap profitability in plastics and packaging company listed on the Indonesia Stock Exchange. The approach used in this study is the associative approach. Sources of data in this study are plastic and packaging companies listed in Indonesia Stock Exchange from 2008 until 2011. Independent variables used in this study consisted of cash turnover and inventory turnover, while the dependent variable is the profitability (ROE). Data collection techniques in this study using techniques of documentation. Data analysis techniques in this study using multiple linear regression, t-test, f-test and coefficient of determination. Processing of the data in this study using the software program SPSS (Statistics Package for the Social Sciens) 16.0 for Windows. The results of this study prove that the partial cash turnover has no significant effect on profitability and inventory turnover partially have a significant effect on profitability. And simultaneous cash turnover and inventory turnover have a significant effect on profitability in plastics and packaging company listed on the Indonesia Stock Exchange.